2015
DOI: 10.1002/jts.21986
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Intimate Partner Violence Perpetration: Results From a National Epidemiologic Survey

Abstract: This study presents data on the association of intimate partner violence (IPV) perpetration and rates of psychiatric disorders, and other correlates. Data were drawn from Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a nationally representative sample of adults in the United States, 18 years and older, residing in households and group quarters. The sample comprised adults who reported being in a relationship within the past 12 months (N = 25,631). Of these, 1,677 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 25 publications
5
61
3
4
Order By: Relevance
“…The literature supports this finding. A number of studies suggest that narcissists tend to commit violence in man-woman and family relationships, and narcissism is positively correlated with being the offender of the violence (Hamberger & Hastings, 1990;Beasley & Stoltenberg, 1992;Craig, 2003;Simmons, Lehmann, Cobb & Fowler, 2005, as cited in Ryan, Weikel & Sprechini, 2008;Carton & Egan, 2017;Okuda et al, 2015). Considering the positive correlation between being the offender and the attitude towards the violence, it can be expressed that this study is consistent with the literature.…”
Section: Discussionsupporting
confidence: 86%
“…The literature supports this finding. A number of studies suggest that narcissists tend to commit violence in man-woman and family relationships, and narcissism is positively correlated with being the offender of the violence (Hamberger & Hastings, 1990;Beasley & Stoltenberg, 1992;Craig, 2003;Simmons, Lehmann, Cobb & Fowler, 2005, as cited in Ryan, Weikel & Sprechini, 2008;Carton & Egan, 2017;Okuda et al, 2015). Considering the positive correlation between being the offender and the attitude towards the violence, it can be expressed that this study is consistent with the literature.…”
Section: Discussionsupporting
confidence: 86%
“…It must be highlighted that only a few studies so far have specifically investigated bidirectional violence; however, the risk factors mentioned have been identified beforesuch as alcohol, tobacco, and illegal drug use. 29,35 Okuda et al 38 have shown that across an extensive variety of factors, the strongest association with violence perpetration is victimization itself, leading to a cycle of escalating violence. Taken together, the present results and the literature about bidirectional IPV indicate that individuals affected by bidirectional violence tend to suffer the most.…”
Section: Discussionmentioning
confidence: 99%
“…These victims have described offenders utilizing a range of violent behaviors (e.g., threats, weapon use, harassing behavior, physical violence, and rape), and half of affected women (45%) and one-quarter of affected men (25%) indicated fearing the perpetrator would cause severe harm and/or death. Surveys of United States perpetrators have displayed intimate partner violence escalating in severity (i.e., with one year between surveys; Okuda et al, 2015), especially with victim attempts to leave the relationship or physically fight back (Jenkins, 2009;Kuijpers et al, 2012). Perpetrators' prior physical aggressiveness, threats to kill, and weapon accessibility correspond with lethal force (i.e., in comparisons between abused women and homicide victims; Jenkins, 2009), and intimate partner homicides tend to follow estrangement.…”
Section: Addressing Remaining Questions About Pre-incident Behaviormentioning
confidence: 99%